Identification of soil degradation during earthquake excitations by Bayesian inference. - Ching, Jianye (Earthquake engineering & structural dynamics.)
A Bayesian inference approach is introduced to identify soil degradation behaviours at four downhole array sites. The approach of inference is based on a parametric time varying infinite impulse response filter model. The approach is shown to be adaptive to the changes of filter parameters and noise amplitudes. Four sites, including the Lotung (Taiwan), Chiba (Japan), Garner Valley (California) and Treasure Island (California) sites with downhole seismic arrays are analysed. Our results show two major types of soil degradation behaviour : the well known strain dependent softening, and reduction in stiffness that is not instantaneously recoverable. It is also found that both types of soil degradation are more pronounced in sandy soils than in clayey soils. The mechanism for the second type of soil degradation is not yet clear to the authors and suggested to be further studied.